Public perspective towards the standardization of Jawi usage on street name signs / Mohd Fauzi Harun - Harun, Mohd Fauzi (2015)
In order to restore the high position of the Jawi, people need to enrich the use of Jawi in the public infrastructures such as road name signs other than in the scientific literature and education system. The road name signs design in certain places such as in Shah Alam and Muar are not only a way finding system but as a platform of enriching the Malay mother tongue writing which is Jawi script other than the Roman words. However, perception towards the implementation is rarely discussed before especially when it comes to the public view as the main audience. Thus, the purpose of this dissertation is to identify the public perception towards the standardization of Jaw; script as part of the road name signs implemented by the local authorities. Their perceptions are important in the implications acceptance, practicality, functionality, identity or sense of bonding aspects. The first phase of the project will involves an interview with two different local authorities in execution of policy for their road name sign system and the local opinions by using survey about their acceptance in Jaw; usage in road name signs. This survey is conducted by using 840 questioners in two different local district councils in Muar and Shah Alam. These aspects will explore the acceptance of Jaw; script adaptation in the road name signs and the reflection of national identity in Jaw; script on road name signs design. The public perspective is important to establish a coordination system, especially when producing a road name sign in a multiracial community. By identifying Jaw; script that can be implemented as part of road name sign design, hence, will allow the other local authorities to take into consideration in having a standard use in the future.